Inhaled corticosteroids' effect on COVID-19 patients: A systematic review and meta-analysis of randomized controlled trials - Yasra Badi; Mohamed Hammad; Abdelrahman G. Tawfik; Mona Muhe Eldeen Eshag; Mahmoud M. Elhady; Khaled Mohamed Ragab; Anas Zakarya Nourelden; Mohamed Hesham Gamal; Ahmed Hashem Fathallah (Canadian Journal of Respiratory Therapy, 2023)
# Background